A study of maintenance management for stadiums in Klang Valley / Zainol Abidin Yang Ahmad - Yang Ahmad, Zainol Abidin (Faculty of Architecture, Planning & Surveying, 2015)
The purpose of this dissertation is to study the maintenance management of stadiums in Klang Valey. This dissertation are meant to identify the type of maintenance management used in stadiums, to identify the issues on maintenance managements and to suggest recommendation for improvement on the quality of maintenance program. Observation on the case study condition and semi-structured interview are conducted to the three involved case study to make data collection and analysis as the primary data resources. The secondary data are collected from journals, articles, documents or handout and internet sources. Based on the result, the types of maintenance management system had been identified which are breakdown and preventive maintenance. The issues that occurs among these case studies are deficiency on maintenance budget, lack of expertise and internal technical staff and quality of work from outsource contractor. Based also on the results, complete planned maintenance programs are recommended to be utilized to the stadiums involved in the case study to ensure the building are in a good condition, have a greater lifespan and safe to be used for athletes and public.